Some structural and emergent trends in Social Housing in Portugal: Rethinking housing policies in times of crisis - Pinto,Teresa Costa (2013)
First of all, this article intends to analyse some structural trends in social housing in Portugal, while relating it with its welfare state regime nature, namely its incipient and tardy character, one that is predominantly oriented towards sectors other than housing. Having other European countries as reference, with different welfare state regimes, we will then point substantive differences in dimension, weight, access forms and target public in this housing sector. Consequently, our main argument revolves around the consequences of a fragile public investment in this domain, which is further channelled in a disparate and bipolar way between a small public promotion of social housing and the incentive to homeownership. We chiefly discuss, as a consequence of this model, the narrowing profile of social housing publics, in a spatially (and temporally) concentrated rationale, gathering individuals with common vulnerability features, lacking the ability to engage in positive residential and social mobility paths. Secondly, we discuss how the current economic and financial crisis, along with profound sociodemographic and labour market changes, determines academics and policy-makers to rethink housing policies and the very role of the state. on the one hand, we are faced with the drastic reduction of state resources and its investment capacity; on the other hand, there is the emergence of new housing needs, as a result of the crisis and also due to more structural economic and social transformations. This context, not only in Portugal but also in Europe, jeopardises policies and housing systems as we now them so far, reintroducing the argument over access (and affordability) to housing by more heterogeneous groups than the common profile of social housing beneficiaries at the moment. We therefore question the role of the state, the rationale and articulation possibilities with other actors and sectors, the financing model and de variety of audiences for whom the right to housing is not yet (or not anymore) guaranteed.